Health of the LGBTI+ Population in Primary Health Care and the Insertion of Nursing - Juliana Spinula dos Santos; Rodrigo Nogueira da Silva; Márcia de Assunção Ferreira (Universidade Federal do Rio de Janeiro, 2019)
Abstract Objective: To reflect on the approaches to the health of the LGBTI+ population, Primary Health Care and Nursing in the care of this population. Method: The reflection is based on a brief characterization of the LGBTI+ population and their health, an analysis of the nurses' work in Primary Health Care (PHC), and a debate about particularities of the nursing care for the LGBTI+ population in the PHC. Results: The LGBTI+ population is composed of many populations defined by the diversity of gender identity and expression, sexual orientation, and biological sex. In Family Health teams, nurses must know the main demands of this population. The institutional reorientation of PHC imposes new challenges to the enjoyment of the right to health of the LGBTI+ population. Conclusion and implications for practice: Although the National LGBT Health Policy is seven years old, studies are still scarce, foremost in Nursing. Considering that the LGBTI+ population is also under the Nursing responsibility in the PHC, it is up to this professional category to provide integral assistance with a view to minimizing the inequalities suffered by this population.